2022
DOI: 10.1177/03635465211072227
|View full text |Cite
|
Sign up to set email alerts
|

Infrapatellar Fat Pad Mesenchymal Stromal Cell–Derived Exosomes Accelerate Tendon-Bone Healing and Intra-articular Graft Remodeling After Anterior Cruciate Ligament Reconstruction

Abstract: Background: Exosomes derived from mesenchymal stromal cells (MSCs) reportedly enhance the healing process. However, no studies have investigated the effect of exosomes from infrapatellar fat pad (IPFP) MSCs on tendon-bone healing and intra-articular graft remodeling after anterior cruciate ligament reconstruction (ACLR). Purpose: To evaluate the in vivo effect of exosomes from IPFP MSCs on tendon-bone healing and intra-articular graft remodeling in a rat model of ACLR. Study Design: Controlled laboratory study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 68 publications
1
51
0
Order By: Relevance
“…Similarly, Huang et al discovered that BMSC-Exos promoted tendon–bone healing after RC reconstruction in rats by inhibiting M1 macrophage polarization and M1 macrophage secretion of pro-inflammatory cytokines to suppress inflammation [ 102 ]. Consistent with these findings, a recent study has shown that IPFP MSC–derived exosomes accelerated tendon–bone healing and intra-articular graft remodeling in a rat model of ACL construction, which may have resulted from the immunomodulation of macrophage polarization, leading to decreasing M1 infiltration while promoting M2 infiltration [ 104 ]. In general, such features of exosomes make them promising tools for attenuating early inflammatory response, which is the prior condition for successful tissue healing processes [ 120 ].…”
Section: Mechanisms Of Msc-exos On Tendon–bone Healingmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, Huang et al discovered that BMSC-Exos promoted tendon–bone healing after RC reconstruction in rats by inhibiting M1 macrophage polarization and M1 macrophage secretion of pro-inflammatory cytokines to suppress inflammation [ 102 ]. Consistent with these findings, a recent study has shown that IPFP MSC–derived exosomes accelerated tendon–bone healing and intra-articular graft remodeling in a rat model of ACL construction, which may have resulted from the immunomodulation of macrophage polarization, leading to decreasing M1 infiltration while promoting M2 infiltration [ 104 ]. In general, such features of exosomes make them promising tools for attenuating early inflammatory response, which is the prior condition for successful tissue healing processes [ 120 ].…”
Section: Mechanisms Of Msc-exos On Tendon–bone Healingmentioning
confidence: 54%
“…Similarly, in a rat RC model, Fu et al reported that ASC-Exo loaded with hydrogels markedly enhanced osteogenic tenogenic and chondrogenic differentiation of tendon stem cells [ 103 ]. Consistent with these findings, a recent study has indicated that infrapatellar fat pad (IPFP) MSC–derived exosomes loaded in a sodium alginate hydrogel promoted tendon–bone healing and intra-articular graft remodeling in a rat ACL construction model [ 104 ]. This may provide a new therapeutic option for the application of exosomes.…”
Section: Current Progress In the Application Of Exosomes To Tbi Injuriesmentioning
confidence: 66%
“…The results of this study provide supportive data for ADMSC young -EVs in tendinopathy therapy and highlight their effects on both tenocytes and macrophages. Two previous studies on ADMSC-derived EVs in tendon repair did not provide the age of donors [ 31 , 32 ]; however, it was natural to conjecture that no ADMSCs from aged mice or humans were used in their studies. Thus, our data were consistent with previous studies, and additional knowledge was provided for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…At 6 and 12 weeks postoperatively, 12 rabbits in each group were sacrificed via a CO 2 overdose, 54 and the cuff-graft-humerus (C-G-H) complexes were carefully dissected for gross examination in bursal- and articular-sided views. The qualitative gross observations were performed by an experienced investigator (W.S.)…”
Section: Methodsmentioning
confidence: 99%